DEVELOPING AKM NUMERACY QUESTIONS IN OKU TIMUR’S AGRICULTURAL CONTEXT USING QUIZIZZ FOR STUDENTS - Nikmah Nurvicalesti; Mewa Zabeta; Dessy Aprima; Amelia Fitriani (Program Studi PGSD Universitas Flores, 2026)
This development research was motivated by the low level of students’ numeracy skills and the lack of contextualized AKM-type questions that relate mathematics to students’ real-life experiences, particularly in agricultural settings. Therefore, this study aimed to develop AKM numeracy questions in an agricultural context for elementary school students, covering numbers, geometry and measurement, algebra, and data. The Tessmer development model was applied through the preliminary, self-evaluation, expert review, one-to-one, small-group, and field-test stages. Preliminary findings showed high student interest in interactive, game-based numeracy questions. Draft I (20 items) was validated by four experts, achieving 78.3% (very valid) and revised to enhance content, context, language, and technical aspects. Practicality tests in the one-to-one (3 students) and small-group (9 students) stages reached 94.44% and 91.39%, respectively (very good), indicating ease of use and understanding. Field testing with 15 students resulted in an average score of 71.4 (good), with 13.3% achieving very good results. Interviews revealed that agricultural-context questions promoted critical thinking, though some students faced challenges. Overall, the agricultural context-based AKM numeracy instrument proved valid, practical, and effective, though findings remain indicative due to the pre-experimental design. Further studies using stronger experimental methods are recommended to confirm its effectiveness.